2014
DOI: 10.1111/hsc.12097
|View full text |Cite
|
Sign up to set email alerts
|

Learning from people with long-term conditions: new insights for governance in primary healthcare

Abstract: Internationally, system-wide changes to the structures and systems governing health care aim to improve outcomes for patients, quality of care and access to services. The introduction of top-down centrally driven solutions to governance of health care, at the same time as increasing policy emphasis on greater 'bottom up' patient and public involvement in all aspects of health care, has set up complex tensions for policy implementation and health care practice. This paper explores the interplay of these agendas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Although patients value continuity of care that is personalised and flexible (Ross et al . ), it is possible clinicians’ consultation routines focus on the technical aspects of diabetes care, and seem to overlook other important aspects of diabetes management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although patients value continuity of care that is personalised and flexible (Ross et al . ), it is possible clinicians’ consultation routines focus on the technical aspects of diabetes care, and seem to overlook other important aspects of diabetes management.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Furler et al (2008) reported that diabetes self-management is more than a technical task, because it also involves difficult social and emotional work. Although patients value continuity of care that is personalised and flexible (Ross et al 2014), it is possible clinicians' consultation routines focus on the technical aspects of diabetes care, and seem to overlook other important aspects of diabetes management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involving users in data collection has both positive and negative impacts, both for those involved and for the results. In the role as data collector, a user can contribute to greater openness in terms of the experiences of the people interviewed and pave the way for a deeper dialogue, producing richer or deeper level data [ 2 , 4 ]. There are challenges as well, not least of an ethical nature, when people with similar experiences meet in the roles of interviewer and interviewee in a research project.…”
Section: Potentials and Challenges Of User Participationmentioning
confidence: 99%
“…With user participation in research, this view of knowledge is problematized and questioned. Users are seen as representatives of various groups and as experts on their situations and conditions [ 2 ]. It is necessary, therefore, to take into consideration the experience and wishes of patients and relatives as well as the relevance and benefit to the field of various activities.…”
Section: Introductionmentioning
confidence: 99%